2016
DOI: 10.1177/0047287516652502
|View full text |Cite
|
Sign up to set email alerts
|

2022 Qatar World Cup: Impact Perceptions among Qatar Residents

Abstract: The purpose of this study was to evaluate how the impacts from the 2022 World Cup preparations in Qatar influenced local residents’ attitudes, personal and community quality of life perceptions, excitement about hosting the event, and support toward the event. The examination of the way mega sport event impacts influence residents’ perceptions of personal and community quality of life is lacking in the literature. Data were collected using systematic sampling in October 2014 from Qatari nationals and white-col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 54 publications
(112 reference statements)
6
66
1
1
Order By: Relevance
“…Taking a new perspective, a different approach [61] to the evaluation of the perceptions (in this case of the tourists) is presented as a way of analyzing the spontaneous annotations of the observed. Literature has already analyzed the perceptions of residents with respect to major events [62][63][64][65][66][67]. A model based on social exchange theory [68] explains the existence of a cause-effect relationship attributable to the cost-benefit dichotomy that can decisively influence the residents' thinking or perception of the event.…”
Section: Residents' Perception Of Sports Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking a new perspective, a different approach [61] to the evaluation of the perceptions (in this case of the tourists) is presented as a way of analyzing the spontaneous annotations of the observed. Literature has already analyzed the perceptions of residents with respect to major events [62][63][64][65][66][67]. A model based on social exchange theory [68] explains the existence of a cause-effect relationship attributable to the cost-benefit dichotomy that can decisively influence the residents' thinking or perception of the event.…”
Section: Residents' Perception Of Sports Eventsmentioning
confidence: 99%
“…As we have seen in numerous scientific contributions that focus on major events [62][63][64][65][66][67]69], the residents' perspective must be taken into account. The present study finds some affinities to the study by Schnitzer et al [73] where the residents were concentrated within a young age range and which took a specific look at the Olympic Games.…”
Section: The Residents' Perception Of Small-scale Sports Events and Dmentioning
confidence: 99%
“…The growth of sport and event tourism has led to a significant increase in research on the impacts of sporting events (Gursoy & Kendall, 2006;Al-Emadi et al, 2016). Preuss (2006) showed that it is not only the public authorities that seek positive legacies but also international sporting entities.…”
Section: A Positive Impacts Of Sporting Mega-eventsmentioning
confidence: 99%
“…It is a fact that the process of hosting a mega-event is complex and requires effort from various stakeholders (e.g. government and private, national, and international initiatives), and in particular, there is a clear need for ever-increasing involvement of the community, not only to facilitate staging the event but also to create a lasting impact on society (Faulkner & Tideswell, 1997;Gursoy & Kendall, 2006;Huang & Zhang, 2012;Kaplanidou, 2012;Nunkoo & Gursoy, 2012;Al-Emadi et al, 2016). For Siegfried and Zimbalist (2000), the decision to designate part of the public budget for staging sporting mega-events precludes the opportunity to prioritize other areas of the budget, notably areas of social demand.…”
Section: Introductionmentioning
confidence: 99%
“…SESRI is in a unique position in year ten of its research program. It has conducted dozens of high quality, timely and substantively relevant survey research projects that have already seen primary use in public policy planning in Qatar, as well as, in peer-reviewed policy-oriented academic journals (Al-Emadi et al, 2017;Diop et al 2016;Gengler and Mitchell, 2018). SESRI management sees opportunities presented by providing materials for reproducible research and the growth in open-access publishing.…”
Section: Data Sharing Culture In the Gulf Regionmentioning
confidence: 99%